Diplomasi Kiai Nahdlatul ‘Ulama (NU) Melalui Konferensi Ulama Internasional - Andi Purwono (SOSIO DIALEKTIKA : JURNAL ILMU SOSIAL HUMANIORA, 2020)
As the largest religious organization, Nahdlatul Ulama has had an international role since its inception. One of these roles is realized through the holding of several international conferences. This article aims to explain the reasons of these conferences and to describe the activities and contributions to the world and especially towards Indonesian foreign policy. This qualitative research used documentary/ literature study in collecting data. The research found that ideational motivation related to the logic of appropriateness (the call) to spread the teachings of Islam rahmatan lil alamin was the reason for the establishment. The conferences gave positive contribution as religious epistemic community, in building network, and in the framework of Islamic and western relations. Towards Indonesian foreign policy, these conferences, firstly emphasized the washathiyah / moderate character of Indonesian Islam which has proven to be compatible with democracy and modernity. Secondly, the thoughts and recommendations generated are valuable inputs for policy makers. Thirdly, the ulama network also has sharpen Indonesia's diplomacy in area Indonesia foreign policy implementation.